Deployment scenarios and applications characterisation for enhanced UMTS simulation - Ferreira, Jaime (2004)
An overview of E-UMTS deployment scenarios and supported services is presented, based on the views of currently relevant players. Deployment and mobility scenarios include expected population density, and usage of service mix, for each environment. Nearly thirty applications are considered. However, a reduced set of applications is needed for simulations purposes, and scenarios were defined with a selection of the most relevant applications. E-UMTS traffic generation and activity models, based on population and service penetration values, are also described and characterised. ON/OFF states have been characterised by appropriate statistical distributions and parameters.